Multimorbidity: Not just for the west - Banerjee A. (2020)
“A multimorbidity lens creates exciting opportunities to reconceptualise health and wellbeing in all its complexity. We need to improve health metrics to capture this complexity and strengthen health services to respond to it.” © 2020 The Author(s).